Synthesis of Benzoyl C-Phenylcalix[4]resorcinaryl Octaacetate and Cinnamoyl C-Phenylcalix[4]arene for UV Absorbers - Budiana I Gusti M. Ngurah; Jumina Jumina; Chairil Anwar; Mustofa Mustofa; Sahadewa Sahadewa (Universitas Gadjah Mada, 2014)
A new upper rim-functionalized benzoyl C-phenylcalix[4]resorcinaryl octaacetate and cinnamoyl C-phenylcalix[4]resorcinarene have been synthesized and evaluated as the absorbers for ultraviolet radiation. The benzoyl C-phenylcalix[4]resorcinaryl octaacetate was synthesized in 3 steps. They were synthesis of C-phenilcalix[4]resorcinarene via acid-catalyzed-condensation of resorcinol and benzaldehyde, followed by O-acetylation and Friedel-Craft benzoylation. The cinnamoyl C-phenylcalix[4]resorcinarene was synthesized in 4 steps. They were synthesis of C-phenilcalix[4]resorcinarene via acid-catalyzed-condensation of resorcinol and benzaldehyde, followed by O-acetylation, Friedel-Craft cinnamoylation and hydrolysis. Spectroscopic analysis (UV) showed that the target molecule absorbed the ultraviolet radiation between 200 and 400 nm with the maximum absorption at 240.50 nm (ε = 10.135 M-1 cm-1) and 243.50 nm (ε = 12.135 M-1 cm-1).